REKONSTRUKSI PARADIGMA PENDIDIKAN AGAMA ISLAM ERA GLOBALISASI - Lazuardi Harahap (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
Gobalization not only enriches the innovative echievements of science and technology, especially, in the aspect of information, telecomunication, and transportation, but also impacts to stimulate degradation of the humanities values and style life of peoples. In one side, globalization endorses liberation and multiinteraction among the peoples,and in other side, it also tends to stimulate fanatism, exclusivism, radicalism, chauvism, and anarchism in the name of tribalism, rascism, religion, sects, and ect. In the context of globalization era, it is important to reconstruct the “old fashion” of classical religious Islamic education with the humanictic-multicultural paradigm. It has tomake its priority in powering how to widespread the universal values of humanity, how to make solidarity in plural societies, how to live together peaceful and harmony with mutual understanding and cooperation among the peoples individually and socially.Therefore, curriculum, matters, metholodologies, tools, sytems of evaluation, and culture of religious Islamic education have to be reformulated